2021
DOI: 10.3390/met11020323
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Pressure-Assisted Diffusion Bonding (IPADB): Review and Outlook

Abstract: Diffusion bonding is a solid-state welding technique used to join similar and dissimilar materials. Relatively long processing times, usually in the order of several hours as well as fine polished surfaces make it challenging to integrate diffusion bonding in other production processes and mitigate widespread use of the technology. Several studies indicate that varying pressure during diffusion bonding in contrast to the traditionally applied constant load may reduce overall processing- and bonding times. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…4 nm 3 at constant temperature and pressure. The curves also indicate a possibility of further decline in volume, as reported in [ 25 ] with impulse pressure assisted. However, it is enough to study the effect of graphene on the sintering process based on the models here.…”
Section: Resultssupporting
confidence: 77%
“…4 nm 3 at constant temperature and pressure. The curves also indicate a possibility of further decline in volume, as reported in [ 25 ] with impulse pressure assisted. However, it is enough to study the effect of graphene on the sintering process based on the models here.…”
Section: Resultssupporting
confidence: 77%
“…Several approaches have been developed in order to reduce the bonding conditions for the diffusion bonding of titanium alloys. The use of varying pressure, interlayers with ceramic nanoparticles or reactive interlayers has been referred to as a potential approach for overcoming the problems in dissimilar diffusion bonding [22][23][24][25][26][27][28]. The use of interlayers in diffusion bonding can reduce the processing conditions and promote the formation of a joint with good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, long durations are generally needed to create a sufficient bond. To reduce processing times, techniques such as the use of interlayers and impulse pressure-assisted diffusion bonding (IPADB), etc., have been investigated, as described in a review paper on IPADB [60]. The results of this study may also be beneficial to reducing the time duration for diffusion bonding of certain metals, as it has been shown that fine compacted titanium powder can be heated within short durations to bond together to achieve near-full density.…”
Section: Densitymentioning
confidence: 99%